The Transformation of Islamic Law in Response to the Development of Digital Society in Indonesia - Muhammadong Muhammadong (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to analyse the evolution of Islamic law in reacting to the growth of the digital society in Indonesia, especially changes in patterns of contact, transaction, communication, and technology-based religious rituals. This study uses a normative juridical approach with a conceptual and statutory approach. The data were gathered via a literature review on the Qur’an, hadith, Islamic legal maxims, fatwas, legislation and related scientific material. The results reveal that Islamic law has an adaptable nature through the process of ijtihad, maqasid al-sharia, maslahah, and fatwa revision. This is evident in the regulation of digital transactions, protection of personal data, platform-based Islamic economics, usage of artificial intelligence, and the transmission of religious information via social media. But these advancements also bring along a number of difficulties such as misinformation, privacy breaches, cybercrime, confusion in electronic contracts and poor levels of digital legal literacy. Islamic law reform must therefore be contextual and collaborative, firmly anchored in the concepts of justice, public benefit, rights protection and moral responsibility. There is a need for a stronger synergy between religious scholars, academics, government institutions, technology industry actors and society in formulating applicable regulations and fatwas that are in harmony with national law and capable of anticipating rapidly evolving and increasingly complex technological developments. The study indicates that the reform of Islamic law is a strategic requirement for the relevance, responsiveness, and ability of sharia rules to provide legal certainty for the digital society of Indonesia.